P–237 The good, the fast and the slow: which is better? Live birth rate following single blastocyst frozen embryo transfer. (6th August 2021) - Sokol, P; Clu. Obradó, E; Inarejos, M Sol; Parrieg. Beltrán, M; Martíne. Sa. Andrés, F; Garcí. Martínez, S; Rodrígue. García, I; Polyzos, N P
Abstract: Study question: Are embryo quality and day of vitrification (Day 5, 6 or 7) associated with live birth rates (LBR) following single blastocyst transfer (SBT) in frozen embryo transfer cycle (FET)? Summary answer: Both blastocyst quality and day of vitrification are significantly associated with LBRs, with very low LBR when poor quality embryos are frozen on day 6. What is known already: Evidence suggests that chromosomal status (ploidy) is strongly associated with blastocyst morphology and good quality embryos are more likely to be euploid. Furthermore, previous studies have shown a relationship between the time that embryos need to reach blastocyst stage and their euploidy rate with slowly developing blastocysts showing higher rate of aneuploidy. Nonetheless, despite all this evidence little is known about the actual effect of the combination of blastocyst quality and day of its vitrification. The scope of this study was to quantify the actual effect of the embryo quality and day of vitrification on live birth rates following FET. Study design, size, duration: Retrospective analysis of 1546 FET cycles with SBT conducted between 2017 and 2019 in the university-affiliated private clinic. The embryos used for FET were obtained from IVF/ICSI: with PGT (FET-PGT) or without PGT (FET0) or from donated oocytes (FET-DON). Participants/materials, setting, methods: FET with natural, natural-modified and completely medicated cycles to prepare endometrial lining were included. Blastocysts were classified according to Spanish Association for the Study of Reproductive Biology (ASEBIR) classification, ranging from A (the highest) to D (the lowest). The impact on LBR of different subgroups, formed within FET-PGT, FET0, FET-DON groups due to different day of vitrification and blastocyst quality, was assessed, using logistic regression after adjusting for age, day of vitrification and embryo quality. Main results and the role of chance: We included 1546 FET cycles. Of those, 543 (35%) corresponded to FET-PGT; 648 (42%) to FET0 and 355 (23%) to FET-DON cycles. Overall, 1051 (68%) embryos were frozen on day 5(D5), 472 (30.5%) on day 6(D6) and 23 (1.5%) on day 7(D7). As far as embryo quality was concerned, 215 (13.9%) grade A; 957 (61.9%) B; 371(24%) C and 3(0.2%) D blastocysts were transferred. LBRs were significantly different between different embryos frozen on D5 44.3%; on D6 28.8% and on D7 8.7%, p < 0.001. When blastocyst quality was considered, LBR were 48.4% for grade A; 42.5% for B; 25.1% for C and 0% for D, p < 0.001. After applying logistic regression analysis, the odds ratio (OR) for transferring D6-blastocyst was 1.08, 95% CI[0.45; 2.62] and blastocyst with grade B and C; 0.71, 95% CI[0.51; 1.00]; 0.57, 95% CI[0.36; 0.88] respectively. However, after transferring D6-blastocyst graded as C, the OR was 0.33, 95% CI[0.12; 0.90]. Our predictive model showed that the impact of the embryo quality on LBR was sustained across three groups. Transfer of D5/D6 grade A blastocyst resulted in the highest, while D6-C in the lowest LBR in all the groups. In the latter case vitrification on D6 impaired additionally the outcome. Limitations, reasons for caution: The study should be interpreted with caution due to its retrospective character and the assessment of blastocyst quality on the day of vitrification and not on the day its transfer. Wider implications of the findings: Our robust findings could be considered a useful tool for counselling couples who seek advice regarding their expected success rates in the setting of FET with SBT. The very low livebirth rates in low quality (C) slow developing (D6) embryos should be communicated to patients prior to planning a FET. Trial registration number: Not applicable